Improving Article Writing Skills through the Implementation of the 3M Method for 12th Grade Students of Senior High School - Aulia Lailatus Siva; Nazurty; Sophia Rahmawati (Institut Agama Islam Negeri Palopo, 2025)
This research is motivated by the low learning activity observed in the teaching of the Indonesian language, particularly article writing, in the first semester of Class XII Science 1 at SMA Negeri 1 Merangin during the 2023/2024 academic year. Out of 31 students, only a few showed good learning outcomes and actively answered the teacher’s questions, while others remained passive, hesitant to ask questions, or distracted during lessons. The aim of this classroom action research (CAR) is to describe the improvement in students' article writing skills through the application of the 3M method (Meniru–Imitating, Mengolah–Processing, and Mengembangkan–Developing). The study was conducted over two cycles during the semester. The results showed that the 3M method effectively improved students' article writing skills. From Cycle I to Cycle II, there was a 12.09% improvement. Overall, from the pre-cycle to Cycle II, the percentage of students achieving scores above the Minimum Competency Criteria (KKM) of 75 increased by 39%. Specifically, there was a 25.81% improvement from the pretest to Cycle I and a further 12.09% increase from Cycle I to Cycle II. Based on these findings, it is recommended that the 3M method be applied to enhance article writing skills among Class XII students at SMA Negeri 1 Merangin.